Comparative sciences interdisciplinary approaches - Wiseman, Alexander W., 1968-; Popov, Nikolay (International perspectives on education and society ;, 2015)
Examining various social science phenomena and comparative studies fields allows for a holistic approach to understanding rather than trying to achieve understanding as a conglomeration of isolated phenomena This volume aims to build a conceptual infrastructure for comparative research. To do this, the capacity for understanding and identifying the comparative method in various fields is necessary. The volume also builds an interdisciplinary base for continued awareness, development and application of comparative studies. Original chapter manuscripts based on papers from the inaugural session of the International Symposium of Comparative Sciences, held in Sofia, Bulgaria (October 2013) are included. Chapters include case studies, regional survey data, cross-national comparisons and other evidence to analyze the complex combination of drivers and characteristics of comparative sciences in all disciplines and fields. The intent is to have a combination of theory-driven syntheses of current scholarship, reports of new empirical research, and critical discussions of major topics related to the practice and study of comparative science.